2016
DOI: 10.1111/jfb.13222
|View full text |Cite
|
Sign up to set email alerts
|

Diel shifts in the structure and function of nearshore estuarine fish communities

Abstract: Day-night shifts in the nearshore fish fauna of a temperate microtidal estuary were assessed using a holistic suite of structural and functional community attributes. Mean fish species richness and diversity (taxonomic distinctness) were higher at night across all regions of the estuary and seasons, concurring with the findings of numerous comparable studies reviewed worldwide, while the diel period in which mean abundance was higher varied among seasons. Likewise, species and functional guild compositions (th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…In June, we observed the occurrence of large individuals of cod, sculpin, flounder and turbot, usually present in a shallowwater area during the night (Lizińska, 2002). Similar regularity was observed during studies of diel shifts conducted by Yeoh et al (2017) in nearshore estuaries where small pelagic fishes were more abundant during the day, while larger pelagic, benthic-pelagic and demersal fishes prevail at night.…”
Section: Nosupporting
confidence: 83%
See 1 more Smart Citation
“…In June, we observed the occurrence of large individuals of cod, sculpin, flounder and turbot, usually present in a shallowwater area during the night (Lizińska, 2002). Similar regularity was observed during studies of diel shifts conducted by Yeoh et al (2017) in nearshore estuaries where small pelagic fishes were more abundant during the day, while larger pelagic, benthic-pelagic and demersal fishes prevail at night.…”
Section: Nosupporting
confidence: 83%
“…Similar regularity was observed during studies of diel shifts conducted by Yeoh et al . (2017) in nearshore estuaries where small pelagic fishes were more abundant during the day, while larger pelagic, benthic-pelagic and demersal fishes prevail at night.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the feeding of aquatic animals, for example, the Yangtze finless porpoise ( Neophocaena asiaeorientalis asiaeorientalis ), was affected not only by environmental factors but also by their diel rhythm (Wang, Akamatsu, Wang, & Wang, 2014; Yerushalmi & Green., 2009). Studying the feeding rhythm of aquatic animals can help adjust the feeding times of cultured species and rationing to improve feed utilization (Yeoh, Valesini, Hallett, Abdo, & Williams, 2017). Specifically, modifying the feeding rhythm could improve animal feeding activity by allowing feed protein to be more readily used for growth, which is of significance in farmed aquatic animal feeding (Gelineu, Medale, & Boujard, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For ABC analysis to provide an accurate indication of environmental condition, the sampling regime must obtain a representative sample of organisms across their full size range (Warwick, 1986). In the current study, ABC analyses were based, however, on samples from just nearshore, shallow waters (< 1.5 m deep), which are dominated by small-bodied species (Hoeksema et al, 2009;Potter et al, 2016;Yeoh et al, 2017). In contrast, the offshore, deeper waters typically contain far greater numbers of larger-bodied individuals (Paterson and Whitfield, 2000;Munsch et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 90%